Applying VRIO Analysis for Strategy Formulation to Increase Competitiveness Through Intangible Asset Mastery (Case Study on Kopi Kita in Padang Ciy) - Fadhil Akbari, Muhammad Farizandani; Hafiz Rahman; Donard Games (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The increasingly fierce competition in the coffee shop industry demands entrepreneurs to have effective strategies to enhance their competitiveness. This research aims to analyze strategies for enhancing competitiveness through the mastery of intangible assets at Kopi Kita in Padang City using the Resource-Based View (RBV) approach and VRIO analysis (Valuable, Rare, Inimitable, Organized). This research uses a qualitative method with a case study, involving observation and in-depth interviews with the owner and branch managers of Kopi Kita. The research results show that mastery of intangible assets, such as competencies, knowledge management, and business networks, plays a strategic role in creating sustainable competitive advantages. Kopi Kita has leveraged competencies in understanding customer preferences, strategic decision-making, product innovation, and problem-solving abilities. In addition, effective knowledge management practices and a wide business network are also key factors in the success of the business. Based on the VRIO analysis, Kopi Kita possesses valuable, rare, hard-to-imitate, and well-organized resources and capabilities, thereby providing a long-term competitive advantage. This study provides theoretical and practical contributions for small and medium enterprises (SMEs) in designing intangible asset-based strategies to enhance competitiveness in the coffee industry.